2016
DOI: 10.1590/s0100-204x2016000900062
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade física e frações da matéria orgânica de um Planossolo sob sistema plantio direto

Abstract: Resumo -O objetivo deste trabalho foi avaliar a qualidade física e as frações da matéria orgânica de um Planossolo sob sistema plantio direto (SPD), com diferentes tempos de implantação, no Sul do Brasil. Amostras de solo foram coletadas nas camadas de 0,00-0,03, 0,03-0,06, 0,06-0,10 e 0,10-0,20 m, tendo-se determinado: a porosidade total (Pt); a macroporosidade (Ma); a microporosidade (Mi); a resistência do solo à penetração (Rp); a densidade (Ds); os macro e microagregados; o diâmetro médio ponderado dos agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
11
0
7
Order By: Relevance
“…Therefore, one of the alternatives to maximize agricultural yields as well as promote soil quality would be the adoption of no-tillage and crop livestock integration systems. Systems such as no-tillage can also induce reductions in greenhouse gas emissions (Ball et al, 2013;Silva et al, 2014), and increase carbon stocks and microbial diversity in the soil (Reis et al, 2016), mainly by the accumulation of surface crop residues.…”
Section: Soil Physical Properties and Their Relation With Vessmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one of the alternatives to maximize agricultural yields as well as promote soil quality would be the adoption of no-tillage and crop livestock integration systems. Systems such as no-tillage can also induce reductions in greenhouse gas emissions (Ball et al, 2013;Silva et al, 2014), and increase carbon stocks and microbial diversity in the soil (Reis et al, 2016), mainly by the accumulation of surface crop residues.…”
Section: Soil Physical Properties and Their Relation With Vessmentioning
confidence: 99%
“…If only higher yields are pursued, the soil structural quality may be compromised, with negative effects on agricultural sustainability in the long term. According to Reis et al (2016), management systems including vegetation cover and control of soil disturbance and machinery traffic, such as the no-tillage system, can benefit soil physical properties in lowlands.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to emphasize that the evaluated management contributed to the maintenance of the soil carbon contents. However, it is worth noting that the efficiency of a system in the recovery of soil quality depends, besides the characteristics of this management, on the degradation process of the soil, such as overpasses, soil exploitation and low production of residues (Reis et al, 2016;Isernhagen et al, 2017).…”
Section: Carbon Management Indexmentioning
confidence: 99%
“…This system improves soil strength to support traffic without presenting significant compressibility due to denser and resistant aggregates (Stone et al, 2006). Reis et al (2016) and Torres et al (2019) observed that the reductions in soil density and soil compaction were related to increments of soil porosity in areas cultivated under NTS with increasing periods of system implantation.…”
Section: Introductionmentioning
confidence: 99%